Glutamine and the effects of exhaustive exercise upon the immune response - Castell, L. M.; Newsholme, E. A. (Canadian Journal of Physiology and Pharmacology, 1998)
There is a high incidence of infections in athletes undergoing intense, prolonged training or participating in endurance races (e.g., the marathon), in particular, upper respiratory tract infections. Prolonged, exhaustive exercise can lower the plasma level of the amino acid, glutamine, which is an important fuel for some cells of the immune system and may have specific immunostimulatory effects. This could therefore be an important factor in the event of an impaired response of immune cells to opportunistic infections. The effects of feeding glutamine to sedentary individuals and to marathon and ultramarathon runners before and after prolonged, exhaustive exercise has been investigated in a series of studies that monitored the incidence of infections and some acute-phase response markers. Oral glutamine, compared with a placebo, appeared to have a beneficial effect on the incidence of infections reported by runners after a marathon.